Comparison of intra-arterial thrombolysis with conventional treatment in patients with acute central retinal artery occlusion. Issue 2 (14th January 2005) - Arnold, M; Koerner, U; Remonda, L; Nedeltchev, K; Mattle, H P; Schroth, G; Sturzenegger, M; Weber, J; Koerner, F
Abstract : Background: Several case series and a recent meta-analysis indicate that intra-arterial thrombolysis (IAT) is effective for the treatment of acute central retinal artery occlusion (CRAO). Methods: A total of 37 patients with acute monocular blindness because of unilateral thromboembolic CRAO were treated with IAT using urokinase within six hours of the onset of symptoms. Visual outcome was compared with a control group of 19 patients, also seen within six hours, who did not undergo thrombolytic treatment. In both groups some patients were treated by paracentesis and/or acetazolamide. Predictors of visual outcome were evaluated. Results: Visual improvement was more likely with IAT (p = 0.01) as were the chances to regain visual acuity of >0.6 significantly better (p = 0.04): 8/37 patients (22%) regained visual acuity of >0.6 in the IAT group and none (0/19) in the control group. Younger patients were more likely to regain some vision with (p = 0.012) or without IAT (p = 0.026). Three patients had minor treatment related cerebral ischaemic events, two had transient ischaemic attacks and one a minor stroke. There were no haemorrhagic complications. Conclusions: This series of patients with CRAO demonstrated that IAT enhanced the chances of visual improvement compared with conventional treatment only. Furthermore, younger patients have a better chance to achieve some visual recovery.